O QUALIS/CAPES como indicador qualitativo de comunicação da ciência: análise da produção acadêmica dos programas de pós-graduação em Ciência da Informação - Autran, Marynice de Medeiros Matos (2015)
QUALIS is a Brazilian official system with the purpose of classifying scientific production (journals, books and conference proceedings) maintained by the Coordenadoria de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). It aims to evaluate qualitatively the scientific literature of Brazilian graduate programs. This research aims to identify which journal titles teachers / researchers of Brazilian graduate programs in information science (PPGCI) convey the production of journal articles in the-five year period 2008-2012. The strata of the journals were identified by WebQualis and scientific production extracted from Curriculum Lattes of teachers / researchers by performing the scriptLattes. In the period investigated the PPGCI produced 1586 articles. 20% of these, were published in stratum A1; 2.4% in stratum A2; 47% in stratum B1; 3.5% in B2; B3 0.7% in B3; 7.5% in B4; 7% in B5; 3.3% in C and 7% in journal without stratum. More than 70% of the articles were published in qualified magazines. Some PPGCIs achieve more than 90%. It was noticed that a significant number of articles were published in journals with stratum C and in those without stratum. These results characterize quantitatively and qualitatively the production of each PPGCI according to QUALIS / CAPES assessment commomly used for evaluation of graduate programs.